Female beauty and male attraction in Ancient Greece: with commentary on the value of the veil and significance of the voice - Massey, Preston T. (Cambridge Scholars Publishing, 2020)
This engaging study documents how ancient Greeks perceived the qualities of female hair as both alluring and attractive, and, therefore, seductive and dangerous. In this sense, ancient Greeks viewed feminine hair differently than it is perceived today. While modern culture can identify with ancient culture by considering a woman's hair to be sexually attractive, ancient Greek culture took this issue one step further by placing an uncovered woman's hair on the same emotional level as a bare breast. One of the principal elements of this historical study is how ancient Greek men tried to deal wit